'A Prolife Disaster': The Reagan Administration and the Nomination of Sandra Day O'Connor. (April 2018) - Flowers, Prudence
The victory of Ronald Reagan in the 1980 presidential election was a victory for a new form of US political conservatism that emphasized both social and economic issues. Abortion was paramount among these new social issues, and opponents of abortion supported Reagan with the belief that he would work vigorously to overturn Roe v. Wade . Less than six months after Reagan's inauguration, the national anti-abortion movement was vociferously condemning the President over the nomination of Sandra Day O'Connor to the Supreme Court. This article explores the nature of the passionate reaction to O'Connor and the fragility of the coalition that opposed her. Anti-abortionists were deeply troubled by the realization that their access and symbolic capital did not translate into influence, and were shocked that abortion was not a litmus test for their 'pro-life President.' The article argues that the relationship between the right-to-life movement, the Reagan administration, and the Republican Party was often fraught, contested, and precarious. In Reagan's first year in office, the place of the right-to-life movement in the new conservatism of the 1980s was remarkably uncertain.